2009
DOI: 10.1021/jf900691r
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Hydrolysis of Fructans in the Tequila Production Process

Abstract: In contrast to the hydrolysis of reserve carbohydrates in most plant-derived alcoholic beverage processes carried out with enzymes, agave fructans in tequila production have traditionally been transformed to fermentable sugars through acid thermal hydrolysis. Experiments at the bench scale demonstrated that the extraction and hydrolysis of agave fructans can be carried out continuously using commercial inulinases in a countercurrent extraction process with shredded agave fibers. Difficulties in the temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 17 publications
1
21
0
1
Order By: Relevance
“…Such conditions seem to reduce the extraction of oils and fats from agave pine cuticles. If agave is cooked in brick ovens by steam injection (brick oven and tahona BAB samples) or in autoclave operations (autoclave BAB), the efficient removal of waxes from agave cuticles is promoted, thereby reducing the possible negative organoleptic properties of the final product [4]. Both the nitrogen and protein contents of BAB samples were slightly higher in crude BAB than in the other biomasses, which is directly related to the less intensive conditions used for inulin extraction for crude BAB than when the agave is cooked in brick ovens and autoclaves as is undertaken with autoclave BAB, brick oven BAB and tahona BAB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such conditions seem to reduce the extraction of oils and fats from agave pine cuticles. If agave is cooked in brick ovens by steam injection (brick oven and tahona BAB samples) or in autoclave operations (autoclave BAB), the efficient removal of waxes from agave cuticles is promoted, thereby reducing the possible negative organoleptic properties of the final product [4]. Both the nitrogen and protein contents of BAB samples were slightly higher in crude BAB than in the other biomasses, which is directly related to the less intensive conditions used for inulin extraction for crude BAB than when the agave is cooked in brick ovens and autoclaves as is undertaken with autoclave BAB, brick oven BAB and tahona BAB.…”
Section: Resultsmentioning
confidence: 99%
“…Other factories carry out fructan extraction (process 3, crude BAB) using diffusers in a manner that is optimized to minimize fructan loss in the residual agave fibers. After carbohydrate extraction, thermal/acid hydrolysis of fructans in autoclaves is carried out under reaction conditions similar to those used when fructans are hydrolyzed directly in the pine before extraction [4]. After coking by processes 1 or 2, the cooked agave is passed through a cutter and shredded using a combination of efficient milling and water extraction to recover sugars for the fermentation stage [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…These results showed a higher increase in plant growth and sugar accumulation between 2 and 4 years after hijuelos plantation, then variations were less pronounced between 4 and 6½ years. Normally, in the tequila elaboration process, the sugar content present in A. tequilana plants at the harvest point was 129-174 g of fructose/ kg of fresh agave head (Avila-Fernandez et al, 2009). As the sugar contain reached at 6½ years was 123.8 ± 0.87 g of sugars/kg of fresh agave head (Table 1), agave plants of this age could be used for the tequila production with a reduction of harvest time.…”
Section: Morphology Total and Free Sugars Contents Of A Tequilana Pmentioning
confidence: 99%
“…Nevertheless, it has to be taken in account that the use of younger A. tequilana plants decreased the ethanol produced during fermentation and increased the methanol content at the end of fermentation as well as changes in the synthesis of other volatile compounds, which could affect the tequila quality (Pinal et al, 2009). Considering the sugar composition of A. tequilana plants, fructose is the principal momoner of the fructan polymers (Lopez et al, 2003), and as it has normally found that at the harvest point (8 years), the A. tequilana juice used for tequila production has 95% of fructose and 5% of glucose (Avila-Fernandez et al, 2009;Cedeño 1995). Therefore, it could be considered that the fructose content in fructans of A. tequilana plants of 6½ years (Table 1) is higher than 90%.…”
Section: Morphology Total and Free Sugars Contents Of A Tequilana Pmentioning
confidence: 99%
“…Recently, the possibility to hydrolyse agave fructans using commercial preparations of fructanases 0308-8146/$ -see front matter Ó 2010 Elsevier Ltd. All rights reserved. doi:10.1016/j.foodchem.2010.08.007 developed for food industry was demonstrated (Munoz-Gutierrez, Rodriguez-Alegria, & Munguia, 2009), and a very recent work described the efforts made to introduce these enzymes in the tequila production process (Avila-Fernandez et al, 2009). However, in that work, efforts were concentrated on a tequila production process different from the traditional one, using modern equipments and, thus not following the traditional steps.…”
Section: Introductionmentioning
confidence: 99%